The Influences of Marketing, Entrepreneurship and Learning Orientations Towards Firm Performance of Malay Entrepreneurs in Perak - Yeop Yunus, Nek Kamal; Abdul Razak, Ahmad Zainal Abidin; Abdul Rahman, Rafiduraida; Goury, Arsalan (Management Research Journal, 2018)
This study aims to uncover the relationship between entrepreneurship orientation, learning orientation and marketing orientation with firm performance among Malay entreprenuers. A total of 240 questionnaires had been distributed to entrepreneurs in major districts in Perak, but only 150 questionnaires were analysed.The data collected was analysed using descriptive and inferential statistical analysis. The findings showed that learning orientation is less contribute to the firm's performance for the entrepreneurs in Perak as compared with marketing orientation and entrepreneurial orientation.The study also found that when marketing orientation increases,performance may also improve. Entrepreneurial orientation was seen to have a strong direct relationship to the firm’s performance. Therefore,an increase on firms’learning orientation will reduce performance while increasing marketing orientation and entrepreneurial orientation, would increase the performance of the firms.